Special features of vocational training institutions in the context of pandemics - Chertakova, Elena M.; Lapshova, Anna V.; Bystrova, Natalia V.; Smirnova, Zhanna V.; Bulaeva, Marina N. (Cuestiones Políticas, 2020)
The coronavirus pandemic has had a profound impact on society. Educational institutions are taking steps to organize the learning process, which will not only preserve, but also improve its quality in the current critical situation. The purpose of the article is to analyze the experience of implementing distance education in the context of the coronavirus pandemic. The distance learning conditions created to guarantee epidemiological safety in order to preserve the health of students and teachers include the use of innovative technological means. We have proposed several solutions to the problems that have arisen in the process of organizing distance education: organizational problems on the technical side of the subject, reducing the burden of teachers and students, organizing effective independent work, and others. It is concluded that the distance learning media and technologies used in the teaching of professional disciplines contribute to the gradual development of the students’ professional competence. The results of the study showed that distance education technologies implemented in the practice of a higher education institution expand the possibilities for students to master educational material.